A practical architecture for implementing end-to-end QoS in an IP network.
All critical elements now exist for implementing a QoS-enabled IP network. It can be built on commercially available platforms and then evolve by adopting emerging standards and technologies. This article describes a practical architecture for end-to-end QoS in an IP environment including incorporation of established, as well as developing, IP and QoS technologies. The article combines the IETF QoS mechanisms with the LAN aspects of QoS and QoS for VoIP-areas usually considered separately. Proposed solutions span across different technologies, e.g., preservation of IP-based classification in MPLS headers, identification of flows encrypted within IPSec during WAN handling, traffic shaping in the access to enable grooming diverse applications and VPNs in the WAN, and so on. VoIP receives special emphasis because of its unique features, such as call setup signaling and call admission control, rarely addressed in traditional IP QoS discussions. An attractive scenario for the IP QoS implementation is to provide a multiservice environment between large enterprise premises over a service provider's core network. A successful end-to-end realization of this service presumes well-defined interworking between the SP's and customers' networks. It will take place on several levels including IP signaling, VoIP setup and CAC, policy interworking, and exchange of billing information. The article recommends to establish SP's presence at the enterprise premises and to implement interworking entities such as the proposed QoS customer server and QoS network server
Keywords: CAC; IETF; IP network; IP signaling; IP-based classification; IPSec; LAN; LAN routers; MPLS headers; QoS customer server; QoS mechanisms; QoS network server; VoIP; VoIP setup; WAN handling; Billing information exchange; Call admission control; Call setup signaling; End-to-end QoS; Enterprise premises; Flow identification; Interworking entities; Multiservice environment; Policy interworking; Practical architecture; Service provider; Standards; Traffic shaping